Pengaruh Financial Leverage , Roi, Roe, Reputasi Auditor, dan Reputasi Underwriter terhadap Tingkat Underpricing Saham pada Saat IPO di BEI - Assari, Hestytia Nirmala; Juanda, Ahmad; Suprapti, Eny (Jurnal Reviu Akuntansi dan Keuangan)
The purpose of this research is to prove that financial leverage, ROI, ROE, auditor reputationand underwriter reputation have an effect on underpricing during IPO. The type of this researchis associative, the population of this study is a company that conducts initial public offering(IPO) in BEI year 2007-2012. Sampling was done using purposive sampling. Types of data usedare qualitative and quantitative data. The results of this study indicate that the variables offinancial leverage (DER), ROI, ROE, Reputation Auditor, and Reputation Underwriter simultaneously affect the level of underpricing of stocks as evidenced by the F-test results of 3.100 witha significance level smaller than 0, 05 which is 0,014. While the test results partially (Test T)shows that only the underwriter reputation only variables that have a significant effect on thelevel of underpricing the stock.Ke ywords: financial leverage, ROI, ROE, auditor reputation, underwriter reputation, underpricing